(untitled) (Sains Humanika, 2013)
Mathematical communication skills of junior secondary school students in coastal area are still considered low due to the lack of contextual problem technique in the teaching of mathematics. The various potencies of the coastal area have been damaged without any concern. It is interesting to investigate the contextual problem in mathematics teaching because it can be identified, required, and related to everyday life. The objective of this study is to enhance mathematical communication skills of junior secondary school students in the coastal area. Using coastal-based contextual teaching and learning (CCTL) can enhance: (1) students’ mathematical communication skills better than conventional teaching and learning (CVTL); and (2) the students’ learning activity, fluency of argument in problem solving process, advanced question skills, and knowledge of coastal area potencies and problems.